PENGARUH BUDAYA KERJA TERHADAP KINERJA PEGAWAI DI SEKRETARIAT KABUPATEN KUTAI TIMUR - Suyatin3, Pranawati1, Eddy Soegiarto2 (EKONOMIA, 2016)
Research problem as follows: What the Work Culture which covers leadership, discipline, motivation, and Science & Technology have a significant effect on the employee performance; What the leadership have a significant effect on the employee performance; What the discipline have a significant effect on the employee performance; What the Motivation have a significant effect on the employee performance; What the science and technology have a significant effect on the employee performance?Purpose of this research is knowing dan analizing the influence of work cultureÂ  which cover leadership, discipline, motivation, and science & technology on the employee performance in East Kutai Regency Secretariat.The Grand Theory used is Human Resource Management. The test questionnaire before conducting research data collection. Test equipment used in this study is Multiple Linier Regression Analysis, Coefficient Correlation (R), Determinant Coefficient (), F test and t test.The multiple linier regression analysis with SPSS 16.0 tools to get results as follows: Y=0,054 + 0,271.X1 +0,182.X2 + 0,303.X3 + 0,270.X4 + e. The value of R 0,717 indicates that the work culture which covers leadership, discipline, motivation, and Science & Technology have a strong relationship to Employee Performance. Value of Determinant Coefficient () 0,514 show that the work culture which covers leadership, discipline, motivation, and Science & Technology take effect to Employee Performance and remaining 48,6 % are influenced by other factors not examined.Based F test which show value 18.519 with probability of significance 0,000. Its mean that the work culture take effect to Employee Performance can generalizable to the population. The work culture which covers leadership, discipline, motivation, and Science & Technology significant effect on the performance of employees together.The Partially shows that The work culture which covers leadership (X1), discipline (X2), motivation (X3), Science & Technology (X4) significant effect to the Employee Working in East Kutai Regency Secretariat. Therefore conclutions based on the results of research conducted hypothesis is accepted.Â